TRENDS IN RESEARCH ON PUBLIC PARTICIPATION IN ELECTION OVERSIGHT: A BIBLIOMETRIC ANALYSIS - Rizal, Taufik; Rusli, A. M.; Syamsu, Suhardiman (Jurnal Administrasi Negara, 2026)
This study aims to analyze the development of research on public participation in election monitoring using a bibliometric approach. This study is particularly important in light of the increasing demands for transparency, accountability, and integrity in democratic governance. The method employed is bibliometric analysis of 332 documents indexed in the Scopus database for the period 2014–2025, using analytical techniques including publication trends, citation analysis, author collaboration, and thematic evolution, supported by VOSviewer and Biblioshiny software. The results show a significant increase in the number of publications, with an annual growth rate of 9.57%, indicating growing academic attention to this topic. Citation analysis reveals that earlier publications have a higher scientific impact, while journal distribution demonstrates a multidisciplinary character, with a strong presence in sustainability and governance-related fields. In addition, the author collaboration network remains fragmented, and research contributions are predominantly dominated by developed countries. The thematic analysis indicates that the main focus revolves around “public participation”, “citizen participation”, and “civic engagement”, with a gradual shift toward more specific and interdisciplinary approaches. In conclusion, research on public participation in election monitoring has developed progressively and remains highly relevant in modern democratic contexts. This study recommends strengthening international collaboration and enhancing the integration of digital technologies to promote more effective public participation.